Classroom interaction in ELTE undergraduate programs: characteristics and pedagogical implications - Lucero, Edgar; Rouse, Megan (Colombian Applied Linguistics Journal, 2017)
This article describes how classroom interaction occurs between teacher educators (TEs) and students in three undergraduate programs of English language teacher education (ELTE) in Bogotá, Colombia. Thirty-four sessions of classroom instruction of nine TEs were observed and transcribed. Data were analyzed under two methodologies—ethnomethodological conversation analysis (ECA) and self-evaluation of teacher talk (SETT). Findings reveal that ELTE classes are divided into transactional episodes that do not necessarily happen in the same order and that are composed of interaction patterns with an extended pedagogical purpose. Further analysis of these interaction patterns unveils that both TEs and students come into the classroom with a pre-planned conversational agenda which contains pedagogical and interactional purposes. Imbalance between both agendas creates instructional paradoxes that send mixed messages to students about how to interact with TEs in class activities. These findings open a discussion on how the identified patterns create a type of classroom interaction that is rather transactional than spontaneous. This discussion in turn contributes to discovering how classroom interaction may occur in ELTE undergraduate programs and how much of it truly achieves pedagogical and interactional goals.